Mathématiques
cmignotcappelle
14

J'ai besoin de votre aide j'arrive pas à développer F= (2x+3)au carré - (x+7)(x-7) G = (3x+1)(x-2)-(2x-3) au carré H = (1/2 + 9x) au carré

+1
(1) Réponses
kimemmamatusi

F = (2x+3)² - (x+7)(x-7) F = (2x)² + 2*2x*3 + 3² - (x² - 7²) F = 4x² + 12x + 9 - x² + 49 F = 3x² + 12x + 56 G = (3x+1)(x-2) - (2x-3)² G = 3x² - 6x +x - 2 - ( 4x² - 12x + 9 ) G = 3x² - 5x - 2 - 4x² + 12x - 9 G = -x² + 7x - 11 H = (1/2 + 9x)² H = (1/2)² + 2*1/2*9x + (9x)² H = 1/4 + 9x + 81x²

Ajouter une réponse